Symbol and intellect in the philosophy of Iamblichus: regarding "De Mysteriis 2.11.20-41" - Hermoso Félix, María Jesús (Logos. Anales del Seminario de Metafísica, 2014)
in this article we discuss the question of the nature of the symbol in the philosophy of iamblichus by analyzing the text of De Mysteriis 2.11.20-41. This text has supported exegesis that sees the symbol as something out of the intellect. According to this interpretation, the symbol would have been introduced by iamblichus to save the weakness of the human soul in relation to the divine, opening the field of theurgy. This framework of interpretation suffers, however, significant shortcomings in providing a deep understanding of the role of the symbol in the philosophy of iamblichus. From the study of the text of De Mysteriis 2.11.20-41, we will approach the symbolic nature, seeking to establish a way of understanding its role in the epistemic process. The relationship of this notion with the term νοερός will be crucial for our study.
Keywords: iamblichus; symbol; knowledge; intellect; Neoplatonism.